Analysis of the Implementation of Character Education through School Culture at SDN 46 Membura, Cemba Village - Umiyati jabri; Aisyah Aisyah; Aminullah Aminullah; Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
SDN 46 Membura Desa Cemba. The research questions are related to the planning, implementation, and evaluation of character education. This research is a qualitative descriptive study consisting of the planning stage, initial data collection, main data, and final data, as well as completion. The research subjects are principals, teachers, employees, students, parents, and residents around the school. Data were collected through interview, observation, and documentation techniques. The validity of the data was obtained through the process of triangulation of sources and methods. Data analysis was carried out through coding and categorizing data as well as data interpretation. The results showed that character education in the culture of SDN 46 Membura Desa Cemba Village, was implemented in the artifact layer as well as values and beliefs. The planning consists of establishing character values, namely religious, disciplined, national spirit, and appreciating achievement; programming; policy socialization; and condition planning. The implementation is through the provision of various program facilities designed to shape the character of students through habituation activities. In general, SDN 46 Membura Desa Cemba has achieved indicators of school success in implementing the four main character values and the value of caring for the environment which is the focus of implementation. Evaluation is carried out through monitoring and evaluation at the end of the semester with the instrument of violation notes and the results of monitoring observations. The evaluation aspects include planning, completeness of facilities, implementation, achievement of targets and comparison of conditions.